The Collateral Damage of In-School Suspensions: A Counterfactual Analysis of High-Suspension Schools, Math Achievement and College Attendance. (June 2023) - Jabbari, Jason; Johnson, Odis
Even the least severe forms of exclusionary discipline are associated with detrimental effects for students that attend schools that overuse them. With a nationally representative longitudinal study of high school students, we utilize propensity score weighting to limit selection bias associated with schools that issue high numbers of in-school suspensions. Accounting for school social order and individual suspensions, we find that high-suspension schools are negatively associated with students' math achievement and college attendance. We also find that when we account for high and low-suspension schools, attending an urban schools is associated with an increase in both math achievement and college attendance.